The Use of Feedback in Classroom Interaction in Moroccan Primary School - Chafi, My Essaid; Elkhouzai, Elmostapha (European Scientific Journal, ESJ, 2016)
This study explores the verbal feedback utilized by a group of Moroccan primary school teachers. The intent is to identify feedback types used and how effective they are in building knowledge and scaffolding thinking. The theoretical framework underpinning this study is embedded within the sociocultural perspective that conceptualizes the classroom as a cultural location of meaning in which relationships, functions, regulations, values, and norms are socially constructed. The study draws on observation data in large-class settings. Twenty two teachers from five different schools took part in the study. Twenty two lessons covering a range of subjects and topics were observed. Verbal manuscripts of classroom discourse were analyzed qualitatively. The analysis of the transcripts revealed that although four different types of feedback were identified, there was little variation in teacher provision of feedback. One particular form was preponderant— evaluative feedback. Interactional issues related to encouraging student responses and thinking are also addressed. Findings reveal that teachers infrequently offer the types of feedback interventions categorized as effective in improving learning during typical classroom interactions. These results are important as they provide an awareness of the feedback practices employed in the observed classrooms and the significant effects they have on classroom interaction and student learning. We conclude by highlighting consequences of these findings on professional development, and offer opportunities for future research.